Board characteristics and Chinese bank performance - Liang, Qi; Xu, Pisun; Jiraporn, Pornsit (Journal of Banking & Finance, 2013)
Using a sample of 50 largest Chinese banks during the period of 2003–2010, we explore a comprehensive set of board characteristics (size, composition and functioning of the board) and analyze their impacts on bank performance and bank asset quality in China. We find that the number of board meetings and the proportion of independent directors have significantly positive impacts on both bank performance and asset quality while board size has a significantly negative impact on bank performance. We find new evidence that the degree of bank boards’ political connection is negatively correlated with bank performance and asset quality. The findings suggest that the board of directors plays a significant role in bank governance in China.